Innovation in feeding practices to improve the sustainability of local and traditional sheep production - Mandaluniz N.; García-Rodríguez A.; Arranz J.; Pineda-Quiroga C.; Beltrán de Heredia I.; Ugarte E.; Ruiz R. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
Small ruminants have played for centuries a key role for the livelihoods of people in the Mediterranean basin. In particular, the importance of dairy sheep systems is evident in relation to landscape configuration, diversity of products, cultural heritage, etc. However, the sustainability of many of these systems is seriously endangered nowadays. Therefore, they will have to face adaptation strategies to fit to the current social, economic and environmental conditions. In particular, feeding practices are related to many of the negative environmental impacts that livestock farming is usually blamed for: methane emissions, landscape degradation and erosion, competition with humans for edible resources, etc. Because of that, the Department of Animal Production of Neiker-Tecnalia is carrying out several research activities relative to the Latxa dairy sheep production system aiming to: (i) innovate in the grazing management practices to enhance the potential of grasslands to fix carbon and improve the fertility of soils, productivity and biodiversity (LIFE REGEN FARMING project); (ii) add value to a range of residues (becoming into co-products) coming from the agrofood industry (dry whey, cold-pressed cakes obtained by the extraction of oil from sunflower, rapeseed and olives) by including them in the ration and decrease the utilisation of soybean, cereals, etc. (LIFE SEEDCAPITAL and VALORLACT projects); and, (iii) improve the nutritive quality and healthy features of added value food products. The rationale behind these activities and some results will be presented.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)